2020
DOI: 10.1038/s41467-020-19232-8
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin-1 receptor-induced PGE2 production controls acetylcholine-mediated cardiac dysfunction and mortality during scorpion envenomation

Abstract: Scorpion envenomation is a leading cause of morbidity and mortality among accidents caused by venomous animals. Major clinical manifestations that precede death after scorpion envenomation include heart failure and pulmonary edema. Here, we demonstrate that cardiac dysfunction and fatal outcomes caused by lethal scorpion envenomation in mice are mediated by a neuro-immune interaction linking IL-1 receptor signaling, prostaglandin E2, and acetylcholine release. IL-1R deficiency, the treatment with a high dose o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
36
0
6

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 28 publications
(47 citation statements)
references
References 51 publications
(89 reference statements)
4
36
0
6
Order By: Relevance
“…In the present study, comparing AA, 5-HETE, 11-HETE, cytokine, and receptor expression demonstrated the absence of glucocorticoid effects. These results, in addition to the results of other studies from our laboratory 3 , suggest that glucocorticoids did not have an effect in our cohort. This was most likely due to the fact that treatment was started late, namely after inflammation has been triggered by infection.…”
Section: Discussionsupporting
confidence: 82%
See 4 more Smart Citations
“…In the present study, comparing AA, 5-HETE, 11-HETE, cytokine, and receptor expression demonstrated the absence of glucocorticoid effects. These results, in addition to the results of other studies from our laboratory 3 , suggest that glucocorticoids did not have an effect in our cohort. This was most likely due to the fact that treatment was started late, namely after inflammation has been triggered by infection.…”
Section: Discussionsupporting
confidence: 82%
“…Contrary to our expectations, glucocorticoids did not alter cytokine production (Table S7). As a result, we suggest that, regardless of whether Covid-19 is treated with glucocorticoids, cross-talk occurs between cytokines, lipid mediators, and ACh, as previously reported 2,3,91 . IL-1 induces 11-HETE 46 ; arterial relaxation induced by ACh is mediated by 11-HETE and is inhibited by indomethacin 43 .…”
Section: Discussionsupporting
confidence: 80%
See 3 more Smart Citations